2014
DOI: 10.1155/2014/624671
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors in Tuberculosis Related Mortalities in Hospitalized Patients

Abstract: Setting. The study was undertaken at the Department of Pulmonology at a public, tertiary care centre in Karachi, Pakistan. Objectives. To evaluate factors concerned with in-hospital deaths in patients admitted with pulmonary tuberculosis (TB). Design. A retrospective case-control audit was performed for 120 patients hospitalised with pulmonary TB. Sixty of those discharged after treatment were compared to sixty who did not survive. Radiological findings, clinical indicators, and laboratory values were compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“… 5 However, it is lower in comparison to China (18.9%), 12 Korea (30.4%), 13 the Philippines (37.5%), 14 and Pakistan (42.5%). 15 The differences in mortality rates between these countries may be due to the difference in the patient populations studied, which could be influenced by ethnic backgrounds and comorbidities. It is important to note that TB mortality rates from long-term studies of ambulatory patients rather than hospitalized patients are generally lower.…”
Section: Discussionmentioning
confidence: 99%
“… 5 However, it is lower in comparison to China (18.9%), 12 Korea (30.4%), 13 the Philippines (37.5%), 14 and Pakistan (42.5%). 15 The differences in mortality rates between these countries may be due to the difference in the patient populations studied, which could be influenced by ethnic backgrounds and comorbidities. It is important to note that TB mortality rates from long-term studies of ambulatory patients rather than hospitalized patients are generally lower.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study indicated that the variable weight had no significant effect on the death and the completion outcome of the treatment. Some studies indicated that low body weight is a risk factor for death [ 28 ] and is also a risk factor for recurrence of the disease. [ 29 ] In contrast body weight at initiation of anti-TB treatment (<35 kg) was an independent predictor for death.…”
Section: Discussionmentioning
confidence: 99%
“…Better understanding of the prognosis factors associated with relapse is an important issue to identify patients at high risk of relapse and promises to reduce the disease burden through risk factors interventions. Several prognosis factors of TB have been reported such as noncompliance to anti-tuberculosis therapy, smoking, longer duration of illness prior to treatment and low body weight (1).…”
Section: Discussionmentioning
confidence: 99%
“…It has been declared as a worldwide health emergency since the last two decades (1). According to annual surveys conducted by the World Health Organization (WHO), 10.4 million cases of TB and 1.7 million deaths occurred in 2016 (2).…”
Section: Introductionmentioning
confidence: 99%